Dundee Ready Educational Environment Measure Tool for Evaluating the Educational Environment: A Systematic Review and Meta-analysis - Farooqi, Faraz Ahmed; Khan, Soban Qadir; Khabeer, Abdul; Ali, Saqib; Al-Ansari, Asim (Open Access Macedonian Journal of Medical Sciences, 2020)
OBJECTIVE: The purpose of this systematic review was to study the literature evaluating the educational environment by using DREEM tool and compute overall mean DREEM score by using Meta-analysis. Further, variation in DREEM score was also studied by distributing studies into different time periods. MATERIALS AND METHODS: A systematic literature search was performed using PubMed and Web of Science databases, followed by review and analysis. All the studies which used DREEM as a tool, published from 1997 to December 2015 were included. Heterogeneity between the studies was assessed by I2-coefficient and Q-statistics. Where significant heterogeneity existed random effect, model was used. Egger’s symmetric test and Begg’s funnel plot was used to study possibility of publication bias. The PRISMA Guideline for systematics review was used. RESULTS: Out of 128 published DREEM studies, 43 passed the criteria and included in analysis. Overall mean DREEM score through Meta-analysis was 2.426 (95% confidence interval [CI]: 2.34-2.52). Studies were divided into two groups for analyzing the time effect. Mean score of the studies published during 1997 to 2009 (group 1) was 2.5 (95% confidence interval [CI]: 2.35-2.64) and for the studies from 2010 to 2015 (group 2) was 2.39 (95% confidence interval [CI]: 2.29-2.5). CONCLUSION: Overall DREEM score was more towards positive side than negative. Current review revealed that DREEM has not been used as predictor for achievement of any medical college instead it can be used to predict high and low achievers in a medical school. This review can signify DREEM to be suitable and consistent tool showing learning environment of institute and student’s prerequisites.